Certain factors affecting first lactation individual monthly milk yields in Frieswal cattle - RAJEEV, RAJEEV; KUMAR, RAVINDER; SINGH, RAJBIR; RAJA, T V; SINGH, Y P; ALI, NAZIM (The Indian Journal of Animal Sciences, 2017)
In the present study, the individual monthly milk yields of 442 Frieswal cows sired by 30 bulls at Military Dairy Farm, Meerut over a period of 8 years (2006–2013) were analyzed to study the effect of various factors. The effect of sire was not significant on any of the monthly yields while the season of calving had significant effect on average milk yields at eighth, ninth and tenth months of lactation. The period of calving had significant effect only on ninth month of lactation while the age at first calving had highly significant effect on yield up to first seven months of lactation. Based on the results, it was concluded that the winter months are the most suitable season for the Frieswal cows to produce more milk and the age at first calving should be maintained at optimum so as to increase the milk production performance of Frieswal cows.